Improving the Quality of Education through Efficient Financial Management: Case Study at Santa Lusia Kindergarten, Indonesia - Saloma Banjarnahor; Eka Daryanto; Restu (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This research aims to investigate and describe the strategic dimensions of educational administration at Santa Lusia Kindergarten Indonesia, specifically focusing on financial management as a driver for quality improvement. The study focuses on four key aspects: (1) budget planning oriented toward educational quality; (2) the organization of human resources; (3) the implementation of financial management; and (4) the financial supervision system. Employing a qualitative descriptive methodology, the research provides an in-depth analysis of administrative practices within the institution. The findings reveal that: First, budget planning is systematically executed through the annual preparation of the school revenue and expenditure plan (RAPBS), involving active stakeholder participation and collective decision-making in meetings chaired by the foundation's head. Second, the mechanism for financial management is inherently linked to its funding sources and the personnel assigned to manage them (the specific organization of human resources remains an ongoing phase of this research). Third, budget implementation is strategically directed toward supporting core school programs, infrastructure development, and the procurement of essential goods and services. Finally, financial supervision is conducted through a collaborative oversight framework involving the Santa Lusia Virgini Foundation and the local Department of Education. Accountability is maintained through a tripartite responsibility structure between the School Committee, the Foundation, and the Education Office, ensuring that financial resources are utilized to sustain and enhance the quality of education.